Nitric Oxide in the Spinal Cord Is Involved in the Hyperalgesia Induced by Tetrahydrobiopterin in Chronic Restraint Stress Rats - Huang, Ying; Jiao, Bo; Zhu, Bo; Xiong, Bingrui; Lu, Pei; Ai, Ling; Yang, Ning; Zhao, Yilin; Xu, Hui (Frontiers in Neuroscience, 2021)
It has been well recognized that exposure to chronic stress could increase pain responding and exacerbate pain symptoms, resulting in stress-induced hyperalgesia. However, the mechanisms underlying stress-induced hyperalgesia are not yet fully elucidated. To this end, we observed that restraint as a stressful event exacerbated mechanical and thermal hyperalgesia, accompanied with up-regulation of nitric oxide (NO) (P < 0.001), GTP cyclohydrolase 1 (GCH1) (GCH1 mRNA: P = 0.001; GCH1 protein: P = 0.001), and tetrahydrobiopterin (BH4) concentration (plasma BH4: P < 0.001; spinal BH4: P < 0.001) on Day 7 in restraint stress (RS) rats. Intrathecal injection of Nω-nitro-L-arginine methyl ester (L-NAME), a non-specific NO synthase inhibitor, or N-([3-(aminomethyl)phenyl]methyl) ethanimidamide, a special inhibitor of inducible NO synthase (iNOS), for seven consecutive days attenuated stress-induced hyperalgesia and decreased the production of NO (P < 0.001). Interestingly, 7-nitro indazole, a special inhibitor of neuronal NO synthase, alleviated stress-induced hyperalgesia but did not affect spinal NO synthesis. Furthermore, intrathecal injection of BH4 not only aggravated stress-induced hyperalgesia but also up-regulated the expression of spinal iNOS (iNOS mRNA: P = 0.015; iNOS protein: P < 0.001) and NO production (P < 0.001). These findings suggest that hyperalgesia induced by RS is associated with the modulation of the GCH1–BH4 system and constitutively expressed spinal iNOS. Thus, the GCH1–BH4–iNOS signaling pathway may be a new novel therapeutic target for pain relief in the spinal cord.